A Companion to the English novel - Arata, Stephen; Haley, Madigan; Hunter, J. Paul 1934-; Wicke, Jennifer (Blackwell companions to literature and culture, 2019)
"Explores the history, evolution, genres, and narrative elements of the English novel, while chronicling its development from the early 18th century to the present day."--Provided by publisher.